A study on the effectiveness of radio ads towards millennials on telecommunication network / Nurul Iman Mohamad Sabari - Mohamad Sabari, Nurul Iman (2018)
The media including television, radio and newspaper have become the essential part of humans’ daily lives. Telecommunication companies in Kuching are constantly putting strategies in place through branding in order to gain more customers and one of it is to advertise on the radio. The study focused on investigating what factors influence the effectiveness of radio ads towards Millennials in Kuching city on telecommunication network. The survey was conducted on a total of 216 respondents comprising of Kuching Millennials bom from the year 1981 to 2000. The sampling technique used were quota sampling and convenience sampling to select the Millennials. There are five factors to be considered in this research on the effectiveness of the radio ads on telecommunication.